Initial results from a realtime FRB search with the GBT - Agarwal, D; Lorimer, DR; Surnis, MP; Pei, X; Karastergiou, A; Golpayegani, G; Werthimer, D; Cobb, J; McLaughlin, MA; White, S; Armour, W; MacMahon, DHE; et al. (Oxford University Press, 2020)
We present the data analysis pipeline, commissioning observations, and initial results from the GREENBURST fast radio burst (FRB) detection system on the Robert C. Byrd Green Bank Telescope (GBT) previously described by Surnis et al., which uses the 21-cm receiver observing commensally with other projects. The pipeline makes use of a state-of-the-art deep learning classifier to winnow down the very large number of false-positive single-pulse candidates that mostly result from radio frequency interference. In our observations, totalling 156.5 d so far, we have detected individual pulses from 20 known radio pulsars that provide an excellent verification of the system performance. We also demonstrate, through blind injection analyses, that our pipeline is complete down to a signal-to-noise threshold of 12. Depending on the observing mode, this translates into peak flux sensitivities in the range 0.14–0.89 Jy. Although no FRBs have been detected to date, we have used our results to update the analysis of Lawrence et al. to constrain the FRB all-sky rate to be 1150+200−180 per day above a peak flux density of 1 Jy. We also constrain the source count index α = 0.84 ± 0.06, which indicates that the source count distribution is substantially flatter than expected from a Euclidean distribution of standard candles (where α = 1.5). We discuss this result in the context of the FRB redshift and luminosity distributions. Finally, we make predictions for detection rates with GREENBURST, as well as other ongoing and planned FRB experiments.